Regulatory elements of the bithorax complex that control expression along the anterior-posterior axis. - Simon, J.; Peifer, M.; Bender, W.; O'Connor, M. (The EMBO Journal, 1990)
The Drosophila bithorax complex (BX-C) controls segmental development by selectively deploying three protein products, Ubx, abd-A and Abd-B, within specific segments along the body axis. Expression of these products within any one segment (or, more accurately, parasegment) is affected by mutations clustered in a particular region of the BX-C. The regulatory regions defined by this genetic analysis span 20-50 kb and there is one region for each segmental unit. Here we describe regulatory elements from several of these regions, identified by fusion to a Ubx-lacZ gene and analysis in germline transformants. A small DNA fragment from the abx region programs expression with an anterior boundary in the second thoracic segment (parasegment 5). This anterior limit is appropriate, since the abx region normally controls Ubx in parasegment 5. Other regulatory regions of the BX-C that control development of parasegments 6, 7 or 8 contain similar regulatory elements that program expression with anterior limits in parasegments 6, 7 or 8, respectively. These experiments define a class of BX-C regulatory elements that control expression along the anterior-posterior axis. The early appearance of the lacZ patterns in embryos suggests a role for these elements in the initial activation of expression from the BX-C.